Increasing the Budget Sustainability of Regions within the Trends of the Economic Development in the Russian Federation (at the Example of the Republic of Karelia) - M. E. Kosov; E. V. Golubtsova; E. S. Novikova (Финансы: теория и практика)
The relevance of the study is determined by the need to ensure the budgetary sustainability of the country’s regions and the importance of state regulation in this process.   The purpose of the paper is to test the hypothesis about the positive impact of the applied instruments of state tax regulation on the level of ensuring budgetary sustainability in the region under consideration.   The objective of this study is to analyze the instruments of government regulation in order to ensure fiscal sustainability in a particular region in the context of transformation of the global economy.   The main methods used in this study include the collection and processing of statistical data, their comparative analysis, the study of the regulatory framework for tax regulation and other documents related to ensuring the budgetary sustainability of territorial units.   The scientific novelty of the conducted research lies in the formation of an approach to the selection of optimal government regulation instruments to ensure the balance of regional budgets.   As a result of the study, tax incentive measures were identified as the most effective among other government support measures aimed at achieving the sustainability of the budgets of the constituent entities of the Russian Federation. The proposed approach allows us to identify tax preferences that, given their temporary nature, will help expand the tax base in the future due to the growth of organizations’ revenues and an increase in the number of taxpayers. It is concluded that it is necessary to use government support instruments that will help unlock the regional tax potential of the Republic of Karelia.   The paper’s significance in practice is its development of a set of specific recommendations for a deliberate transformation of the relevant regional tax laws in the Russian Federation.